DEVELOPMENT OF CANVA-ASSISTED PBL TO IMPROVE STUDENTS’ INFORMATION LITERACY AND CRITICAL THINKING SKILLS - Ani Nur'aeni; Nelly Fitriani; Galih Dani Septian Rahayu (Universitas Majalengka, 2026)
The low level of information literacy and critical thinking skills in elementary school students in 21st-century learning is due to teacher-centered learning, resulting in students being less active in analyzing, evaluating, and using information effectively. This study aims to develop and test the effectiveness of a Problem-Based Learning model assisted by the Canva application in improving students' information literacy and critical thinking skills. This study used a Research and Development (R&D) approach adapted from Borg & Gall with 10 systematic stages. The subjects were teachers and fourth-grade elementary school students in Purwakarta Regency. Data collection was conducted through interviews, Likert-scale questionnaires, observations, and pretests and posttests. Data analysis used both qualitative and quantitative methods. The results of the PBL model's effectiveness test using the Canva application showed an increase in the average score from 57.08 to 78.32 with an N-Gain of 0.49 (moderate category) for information literacy skills, and from 47.6 to 72.6 with an N-Gain of 0.48 (moderate category) for critical thinking skills. The effectiveness test results showed a significance value of less than 0.05, indicating that the model had a significant impact on both skills. This study concludes that the Problem-Based Learning model assisted by the Canva application is effective in improving information literacy and critical thinking skills in elementary school students.